Functional trait changes in the floras of 11 cities across the globe in response to urbanization. Issue 7 (29th August 2016) - Palma, Estibaliz; Catford, Jane A.; Corlett, Richard T.; Duncan, Richard P.; Hahs, Amy K.; McCarthy, Michael A.; McDonnell, Mark J.; Thompson, Ken; Williams, Nicholas S. G.; Vesk, Peter A.
Abstract : Urbanization causes major environmental changes globally, which can potentially homogenize biota across cities through the loss and gain of particular types of species. We examine whether urban environments consistently select for plants with particular traits and the implications of such changes on the functional composition of urban floras. We classified plant recorded in 11 cities around the globe as species that have either colonized (arrived and naturalized), persisted or been lost (local extirpation) following urbanization. We analyzed how 10 traits previously linked with plant responses to environmental conditions explained membership of these three groups, by comparing colonisers with persistent and extirpated plants through individual city‐level Bayesian models. Then, we used meta‐analysis to assess consistency of traits across urban areas. Finally, we explored several possible scenarios of functional change using these results. On average, urban colonizers had heavier seeds, unspecialised nutrient requirements, were taller and were annual species more often, especially when compared to locally extirpated plants. Common trends of functional change in urban plant communities include shifts towards taller and heavier‐seeded plants, and an increased prevalence of the short‐lived species, and plants without mutualistic nutritional strategies. Our results suggest that plant traits influence the species that succeed in urban environments worldwide. Different species use different ecological strategies to live in urban environments, as suggested by the importance of several traits that may appear as trait constellations. Plant height and seed mass were the only traits associated with both colonizer and extirpated plant status in urban environments. Based on our data, predicting colonization in urban environments may be easier than identifying extirpation‐prone plants; albeit some regional variation, colonization seems strongly driven by environmental conditions common to most cities (e.g. altered disturbance regimes), whereas extirpation may depend more on processes that vary across cities.